After the Strike? Part 1: The Transitional Space of the Picket Line. Issue 2 (3rd April 2021) - Rendell, Jane
Abstract: This essay explores the activities of strikers at the Bartlett School of Architecture, UCL over a 14 day-period in the early spring of 2018. These days were part of the 2018 University and College Union (UCU) Pension Strike, one of the largest strikes of university academics in recent times, which occurred over a 4-week period, with strike days increasing from two days in the first week, to five by the final week. This was a strike to protect the pensions of university workers as a defined benefit scheme rather than a defined contribution one. This essay is structured as a two-stranded diary, weaving together textual materials taken from the Strike chronicle and website produced at the time, with critical reflections written in the present, concerning the current state of the neo-liberal university, discussing issues relating to pensions – namely institutional critique, ethics and equity, labor and work, precarity and care.